2022
DOI: 10.1542/peds.2021-055571
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Childhood Obesity: A Systematic Review

Abstract: BACKGROUND AND OBJECTIVES: Addressing food insecurity while promoting healthy body weights among children is a major public health challenge. Our objective is to examine longitudinal associations between food insecurity and obesity in US children aged 1 to 19 years. METHODS: Sources for this research include PubMed, CINAHL, and Scopus databases (January 2000 to February 2022). We included English language studies that examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 34 publications
3
22
0
2
Order By: Relevance
“…In general, there is controversy in studies regarding the association between HFI and childhood overweight/obesity, although it seems that large cross-sectional studies and systematic reviews have shown a positive association [17,20]. In our study, we found an independent association between the HFI and childhood overweight and obesity.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…In general, there is controversy in studies regarding the association between HFI and childhood overweight/obesity, although it seems that large cross-sectional studies and systematic reviews have shown a positive association [17,20]. In our study, we found an independent association between the HFI and childhood overweight and obesity.…”
Section: Discussionsupporting
confidence: 42%
“…Its relationship is controversial and its association is not yet clear. Although numerous studies in developed countries found a positive relationship between HFI and childhood obesity [14][15][16][17] , others did not observe any association [18][19][20], and some detected an inverse association [21].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence for a causal relationship of household food insecurity with childhood obesity has been mixed, and no studies to date have examined clinically‐based food security interventions on childhood obesity outcomes 18 . This research is the first to demonstrate that a clinical‐community partnership to deliver a mobile food pantry program in a clinical setting may help reduce childhood obesity among a population disproportionately burdened by obesity.…”
Section: Discussionmentioning
confidence: 87%
“…Given the high and rising prevalence of obesity and household food insecurity among children, effective clinical interventions to reduce childhood obesity in households with food insecurity are needed 13,14 . Alleviating food insecurity may help reduce childhood obesity because household food insecurity has been linked to unhealthy dietary factors and childhood obesity 15–18 …”
Section: Introductionmentioning
confidence: 99%
“…Health inequalities exist throughout the world. In particular, food insecurity affected 14.8% of US households with children in 2020 and has been correlated with childhood obesity [ 53 ]. In the US, toddlers living in households with limited incomes may be supported by US federal government programs, such as Special Supplemental Nutrition Program for Women, Infants, and Children, and Supplemental Nutrition Assistance Program, among others [ 13 ].…”
Section: Feeding and Nutrition Challenges During Young Childhoodmentioning
confidence: 99%